Oral metastasis of chondroblastic osteosarcoma - Rakesh Kumar Dumpala; Venkateswara Rao Guttikonda; Sivaranjani Yeluri; Jayakiran Madala (Wolters Kluwer Medknow Publications, 2012)
Osteosarcoma is the most common primary malignant mesenchymal tumor, accounting for approximately 20% of sarcomas, with 5% incidence in the jaws. They present various clinical and histological aspects as well as variable disease prognosis and outcome. About 50% of all osteosarcomas are osteoblastic, 25% fibroblastic, 25% chondroblastic. Metastasis of osteosarcoma in the oral cavity is rare, and very few cases have been described so far in the literature. This article presents a metastatic case of chondroblastic osteosarcoma in the mandibular right-attached gingiva arising from 4 th rib. This case report further suggests that chondroblastic osteosarcoma has poor prognosis.